2022
DOI: 10.1152/ajplung.00388.2021
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated activation of CFTR via prostaglandin signaling pathways in the airway

Abstract: Cystic fibrosis (CF) is a genetic disease caused by mutations of the gene encoding a cAMP-activated Cl- channel, the cystic fibrosis transmembrane conductance regulator (CFTR). CFTR modulator therapies consist of small-molecule drugs that rescue mutant CFTR. Regimens of single or combinations of CFTR modulators still rely on endogenous levels of cAMP to regulate CFTR activity. We investigated CFTR activation by the natural mediator prostaglandin E2 (PGE2) and lubiprostone and tested the hypothesis that recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This experimental technique was applied in a wide array of research areas, including the study on the mechanisms of diarrheal disease in the setting of Salmonella infection and on the regulation of epithelial chloride secretion by the epidermal growth factor receptor [33], and the research on the cytotoxic effect of smoke from polymer combustion on human lungs [32]. For a long time, the Using chamber systems have been the most frequently used for the study of intestinal epithelium [34], but more recent papers describe the research on the airway epithelia, including the targeting of prostaglandin receptors in cystic fibrosis (CF) treatment [35].…”
Section: Ussing Chambermentioning
confidence: 99%
“…This experimental technique was applied in a wide array of research areas, including the study on the mechanisms of diarrheal disease in the setting of Salmonella infection and on the regulation of epithelial chloride secretion by the epidermal growth factor receptor [33], and the research on the cytotoxic effect of smoke from polymer combustion on human lungs [32]. For a long time, the Using chamber systems have been the most frequently used for the study of intestinal epithelium [34], but more recent papers describe the research on the airway epithelia, including the targeting of prostaglandin receptors in cystic fibrosis (CF) treatment [35].…”
Section: Ussing Chambermentioning
confidence: 99%
“…Lubiprostone, approved for the treatment of chronic constipation [ 73 ], stimulates fluid secretion via activation of the CFTR channel through prostaglandin receptor EP4 mediated modulation of cAMP levels [ 74 ]. Recently, Shaughnessy and colleagues reported enhanced F508del rescue in CF airway epithelia when Trikafta™/Kaftrio™ was combined with lubiprostone [ 75 ]. The dual phosphodiesterase 3 and 4 inhibitor RPL554 (ensifentrine), in clinical development for chronic obstructive pulmonary disease (COPD) and asthma [ 76 ], was shown to activate CFTR with rare class III and IV mutations [ 77 , 78 ] and was tested in a small phase II trial with promising results ([ 79 ] & NCT02919995).…”
Section: Cftr Causal Therapiesmentioning
confidence: 99%
“…The CFTR chloride channel is known to be involved in secretory diarrhea 28 and is activated by the PGE 2 and PG receptor agonist lubiprostone 29 . In addition, a previous report suggested that the inhibition of CFTR reduced fluid secretion in infectious secretory diarrheas 30 .…”
Section: Discussionmentioning
confidence: 99%